La familia en el desarrollo de la autonomía en niños de 4 a 5 años en la Unidad Educativa Fernando Daquilema, Ciudad de Riobamba - Guerra Naranjo, Daniela Lizbeth (2023)
This research was carried out at the Fernando Daquilema Educational Unit in the city of Riobamba, Province of Chimborazo, to identify the importance of the family and how it can influence the development of autonomy in children from 4 to 5 years old, given that the role of parents or caregivers, as well as their rules, are of great relevance for their development. For this purpose, a non-experimental study was carried out in which bibliographic, documentary, and descriptive research was presented, which will allow the analysis of those above, with a population of 30 students from 4 to 5 years old. For the study, a survey was applied to parents whose information allowed the tabulation, analysis, and interpretation of different critical questions about the autonomy of their children and, in the same way, to reach conclusions and recommendations. Through the survey, it was possible to observe that the answers vary depending on the type of family, rules of the caregivers, emotional ties, and socioeconomic level, among other factors, which could be analyzed and thus obtain excellent results for the research.